Effects of growth regulators on in vitro propagation of Sophora tomentosa L. (Necklace pod) - Rungprateeppaiboon, N.; Chareonsap, P. P.; Pongtongkam, P.; Poeaim, A.; Poeaim, S. (My University, 2024)
Seeds of Sophora tomentosa were sterilized and germinated on MS medium with BAP (1 mg/L), which was observed to be 75% germination rate with the highest amount of multiple shoots (3 shoots per seed) and an average length of 29.56 mm. The germination rate was reduced to 33.33% by 1% NaCl. Multiple shoot induction was worked on MS medium with 2.0 mg/L of TDZ that induced the highest shoot bud formation rate (46.67%) with the highest amount of shoot bud (10.71 buds per culture), while 1.0 mg/L GA3 showed the highest average length of 34.13 mm. For root induction, 20% rooting was formed in 1/2 MS medium with a combination of 0.5 mg/L IAA and BAP with 0.1% AC, with 3 roots per culture and an average root length of 15.36 mm. After acclimatization for 16 weeks, 70% of the plantlets successfully survived.
Keywords: Acclimatization; Multiple shoot induction; Root induction; Sophora tomentosa